Redescription of Tetragonurus pacificus (Teleostei: Stromateoidei: Tetragonuridae), based on specimens collected from Taiwan and Tarawa Atoll - Koeda, Keita; Teramura, Akinori (Zootaxa, 2019)
The rare squaretail Tetragonurus pacificus Abe 1953 was described on the basis of a single poor-condition specimen obtained from the stomach of a yellowfin tuna collected from west of the Solomon Islands. A fresh specimen of T. pacificus was recently collected from southwestern Taiwan and its morphology and the fresh coloration are herein described in detail. In addition, a juvenile specimen collected from the southern Pacific Ocean was found in the museum collection. The species is characterized by dorsal-fin spines 10–11; longitudinal scale rows along body axis 72–80; and predorsal scales 17–20. The present specimen collected from off southwestern Taiwan represents the northernmost record of the species from the Pacific Ocean.